Bribery vs. extortion: allowing the lesser of two evils - Fahad Khalil; Jacques Lawarrée; Sungho Yun (Center for Economic Studies and ifo Institute (CESifo), 2007)
Rewards to prevent supervisors from accepting bribes create incentives for extortion. This raises the question whether a supervisor who can engage in bribery and extortion can still be useful in providing incentives. By highlighting the role of team work in forging information, we present a notion of soft information that makes supervision valuable. We show that a fear of inducing extortion may make it optimal to allow bribery, but extortion is never tolerated. Even though both increase incentive cost, extortion penalizes the agent after good behavior, while bribery penalizes the agent after bad behavior. Since bribery occurs when a violation is detected, the bribe is a penalty for bad behavior, and helps somewhat in providing incentive. We find that extortion is a more serious issue when incentives are primarily based on soft information, when the agent has a greater bargaining power while negotiating an illegal payment, or when the agent has weaker outside opportunities. Our analysis provides explanations why extortion may be less of a problem in developed countries.
Keywords: D82; L23; 330; Kontrolle; Organisationsstruktur; Anreizvertrag; Korruption; Framing; Theorie